Endoscopic ultrasonography can detect a cause in the majority of patients with idiopathic acute pancreatitis: a systematic review and meta-analysis - Umans, Devica S.; Rangkuti, Carlos K.; Sperna Weiland, Christa J.; Timmerhuis, Hester C.; Bouwense, Stefan A. W.; Fockens, Paul; Besselink, Marc G.; Verdonk, Robert C.; van Hooft, Jeanin E.; for the Dutch Pancreatitis Study Group (Endoscopy, 2020)
Background Idiopathic acute pancreatitis (IAP) has a 25 % pancreatitis recurrence rate. Endoscopic ultrasonography (EUS) may diagnose treatable causes of IAP and hence prevent recurrence. The goal of this systematic review with meta-analysis is to determine the diagnostic yield of EUS and its impact on recurrence.Methods PubMed, EMBASE and the Cochrane Library were systematically searched for English studies on EUS in adults with IAP. The primary outcome was diagnostic yield. Secondary outcomes included recurrence. Methodological quality was assessed using the QUADAS-2 score. Meta-analysis was performed to calculate the pooled diagnostic yield and risk ratio with 95 % confidence intervals (CI) using a random-effects model with inverse variance method.Results 22 studies were included, with 1490 IAP patients who underwent EUS. Overall diagnostic yield was 59 % (874 /1490; 95 %CI 52 % – 66 %). The most common etiologies were biliary (429 /1490; 30 %, 95 %CI 21 % – 41 %) and chronic pancreatitis (271 /1490; 12 %, 95 %CI 8 % – 19 %). In 2 % of patients, neoplasms were detected (45 /1490; 95 %CI 1 % – 4 %). There was no difference in yield between patients with or without recurrent IAP before EUS (risk ratio 0.89, 95 %CI 0.71 – 1.11).Conclusions EUS is able to identify a potential etiology in the majority of patients with IAP, detecting mostly biliary origin or chronic pancreatitis, but also neoplasms in 2 % of patients. EUS may be associated with a reduction of recurrence rate. Future studies should include complete diagnostic work-up and preferably include patients with a first episode of IAP only.